Achieving sustainability in sharing-based product service system: A contingency perspective. (15th January 2022) - Li, Dun; Huang, Youlin; Sun, Hui; Zhi, Bangdong
Abstract: The purpose of this study is to provide empirical evidence for the sharing-based product service system (sharing-based PSS), a new type of PSS, to achieve sustainable performance in sharing economy context. A multiple case study method was applied, in which 20 semi-structured interviews were conducted with key respondents from three transport sharing economy companies (i.e., OfO, Mobike, and Man-bang) in China. We found that the structural and infrastructural aspects of the service delivery system design influence the achievement of sustainability for sharing economy platforms. Moreover, by applying contingency theory, this study identified goal congruence and application of information and communications technology as contingent factors that affect the relationship between the service delivery system design and the sustainability initiatives. This study provides insightful knowledge into the sharing-based PSS and therefore has enormous practical implications for sharing economy platforms. Highlights: We analyze sustainability of sharing-based product service systems (PSS). 20 interviews with key people from three sharing economy companies were conducted. Structural and infrastructural aspects affect sustainability of sharing economy firms. Goal congruence and application of ICT as contingent factors in sharing economy.